Distributional impact assessment of policy changes to old-age pensions, social benefits and taxes in Lithuania (2021–2024) - Jekaterina Navickė; Vitalija Gabnytė-Baranauskė (Lithuanian Journal of Statistics)
Assessing the distributional impact of policy reforms is a crucial component of the policy planning and implementation cycle. This paper provides a comprehensive follow-up to the 2021 study on nowcasting poverty and inequality in the context of economic growth and Covid-19 pandemic in Lithuania, prepared by the authors of the present work. Here we extend the analysis for the period of 2021–2024. We examine the impact of recent policy changes to old-age pensions, social benefits and direct taxes following the Covid-19 pandemic, focusing on key distributional indicators, such as the at-risk-of-poverty rate (AROP), income inequality (measured by the inter-quintile ratio (S80/S20) and the Gini coefficient), and a nationally applied measure of absolute poverty. The analysis utilizes the tax-benefit microsimulation model EUROMOD. The results obtained indicate a consistent decline in AROP and income inequality in Lithuania between 2021 and 2024, primarily due to adjustments in old-age pensions, rather than changes in direct taxes, social insurance contributions or other social benefits. However, these adjustments only partially mitigate the effects of high inflation. As a result, the absolute poverty rate is estimated to exceed its 2021 levels by 2–4 percentage points between 2022 and 2024.